2018
DOI: 10.17576/jsm-2018-4707-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medicated and Non-medicated Multi-nutrient Block Supplementation on Gastrointestinal Parasite Infestation and Blood Hematological Parameters of Lactating Saanen Goats

Abstract: In a 90-day feeding trial, twenty four (24) Saanen lactating does were assigned to four treatment group. The treatments were feeding: basal diet only as a control (T1), basal diet with urea molasses multi-nutrient block (UMMB) (T2), basal diet with medicated urea molasses multi-nutrient block (MUMB) (T3) and basal diet with commercial mineral block (CMB) (T4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Concerning the effect of period of treatment of I on hematological parameters, the time period had a significant effect on RBC (P=0.04), PLT (P<0.001), GRA (P=0.035) and Lymph (P=0.005) Table 1. The overall means of the hematological parameters of the current study are within the normal ranges which were reported previously by Manohar et al (2021), Arfuso et al (2016) and Panadi et al (2018). Studies concerned the effect of period of treatment of I drenching on hematological parameters in goats during late pregnancy are rather limited.…”
Section: Results and Discussion Blood Hematology Parameters Of Black ...supporting
confidence: 86%
“…Concerning the effect of period of treatment of I on hematological parameters, the time period had a significant effect on RBC (P=0.04), PLT (P<0.001), GRA (P=0.035) and Lymph (P=0.005) Table 1. The overall means of the hematological parameters of the current study are within the normal ranges which were reported previously by Manohar et al (2021), Arfuso et al (2016) and Panadi et al (2018). Studies concerned the effect of period of treatment of I drenching on hematological parameters in goats during late pregnancy are rather limited.…”
Section: Results and Discussion Blood Hematology Parameters Of Black ...supporting
confidence: 86%
“…Experiences from several countries indicate that the supplementation with MBs resulted in substantial increase of productive, reproductive and economic performances of goats, bulls cows, in different systems of animal production (Lawania & Khadda, 2017;Patil, Verma, Singh, Das, & Gaur, 2017;Tekeba, Wurzinger, Baldinger, & Zollitsch, 2013;Tiwari, Shrestha, Mandal, & Panday, 2012). Ben relates that, according to economic analysis made in different researches, it has been established that the usage of multi-nutrient blocks presents economic revenue as in confinement as in pasture.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, salt block supplementation is commonly practised to overcome mineral deficiencies in ruminants; however, most of the salt blocks in the local markets are imported and not purposely to solve protein and energy deficiencies (Panadi et al, 2018). Due to these issues, urea-molasses mineral blocks (UMMB) or eISSN Number: 2462-2389 © 2022 UMK Publisher.…”
Section: Feed Technologymentioning
confidence: 99%